Small cell carcinoma of the ovary, pulmonary type: A role for adjuvant radiotherapy after carboplatin and etoposide? - Anase S. Asom; Ricardo R. Lastra; Yasmin Hasan; Lori Weinberg; Gini F. Fleming; Katherine C. Kurnit (Elsevier, 2022)
Background: Primary small cell ovarian cancer of pulmonary type (SCCOPT) remains a rare ovarian tumor. Its aggressive nature is associated with poor survival outcomes. Current treatment algorithms rely on systemic chemotherapy, primarily involving platinum agents. However, given its low incidence, less is known about the potential benefits of other treatments. Case Presentation: We report a case of an 80-year-old woman who was found to have a complex pelvic mass with a mildly elevated CA-125. She underwent a laparotomy for staging with tumor debulking; she had bulky unresectable adenopathy and pathology was consistent with stage IIIC SCCOPT. Postoperative imaging revealed progression of disease. She received six cycles of carboplatin and etoposide followed by consolidative radiation therapy to her para-aortic lymph nodes. She remains disease-free for over four years after completion of adjuvant therapy. Discussion: Histologically, SCCOPT resembles small cell carcinomas of the lung, which are treated with a combination of chemotherapy and radiation therapy. New approaches that build upon the current treatment approaches and incorporate strategies from non-gynecologic tumor types could be beneficial.